The impact of the shadow economy on the official economy in sri lanka - Reginold, L. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Currently the concept of the shadow economy is the most talking issue. World bank and IMFdo lot of researches to measure the domination of shadow economy all over the world and issue varies reports based on it. Not only that, every country also gives important to measure the size and impact of shadow economy on the official economy. That is why this studyanalyses the impact of the shadow economy on the official economy in Sri Lanka.For this Study, Time series data were collected between 1990 and 2017, and multiple regression was used to find out the relationship and ordinary least squares technique was used to estimate the Multiple regression model. Finding of this study emphasizes that the shadow economy has negative and significant impact on the official economy in Sri Lanka. The coefficient of the shadow economy is – 0.13it meansif the size of the shadow economy decreases by 1 percent, the official economy will increase by 0.13 percent. And alsocapital has a positive and significant impact on the official economy whereas labour force has a negative and significant impact on the official economy. It was therefore recommended that the government should take following measuressuch as reducing high tax rate, Simplifying the tax system and making it easy to understand by the public, Taking legal action against the people who are tax evasion, Reducing the social welfare payment, Receiving state revenue from other sources rather than tax sources and People need to be educated about the purpose of the taxation and obligationto control the shadow economy.
Keywords: Sri Lanka; Official economy; Shadow economy; Capital Labour force